TaTCP6 is required for efficient and balanced utilization of nitrate and phosphorus in wheat - Bin Liu; Weiya Xu; Yanxiao Niu; Qiuyuan Li; Beilu Cao; Jingyi Qi; Yidi Zhao; Yilan Zhou; Long Song; Dongkai Cui; Zhenshan Liu; Mingming Xin; et al. (Nature Communications)
Abstract High crop yields require adequate nutrients, particularly nitrate (N) and phosphorus (P). Identifying regulators for efficient N-P utilization is critical in wheat. To explore N-P interactions, we analyze root transcriptomes under varying N-P supplies and identify TaTCP6 as a potential regulator. Nitrate-stimulated TaTCP6 directly triggers the expression of genes related to nitrogen utilization. TaTCP6 competes with TaSPX1/4 for the release of TaPHR2, and also interacts with TaPHR2 to enhance the transactivation capacity of downstream genes. Thus, through the dual roles of TaTCP6, the TCP6-SPX-PHR2 module activates the expression of phosphorus starvation response (PSR) genes. Inhibiting TaTCP6 reduces N and P absorption, negatively impacting yield, while overexpressing TaTCP6 increases grain yield. Notably, overexpression of TaSPX1 suppresses nitrogen utilization genes, especially under low phosphorus conditions. In conclusion, our findings highlight the role of TaTCP6 in coordinating N and P utilization and propose a strategy to reduce fertilizer inputs for sustainable agriculture.